INVESTIGATION OF CONSUMER PREFERENCES REGARDING FOODS LABELING AND QUALITY ASSESSMENT - Tikhonova O.Y.; Reznichenko I.Y.; Zorkina N.N. (Техника и технология пищевых производств, 2015)
Modern and civilized consumption of foods should include the freedom to choose quality goods. At the heart of the buyer choice is a complete access to information about the foods which is provided by the manufacturer or a seller. Therefore, it is extremely important to ensure comprehensibility, adequacy and reliability of the labeling of goods as a source of important information about them, their properties and packaging. A reliable, accessible and readable label should be an inherent part of a product. A label is the main source of information about the product, both for the end consumer and for various trade organizations. To identify consumer preference regarding the quality of food labels in the market of foods and the degree of importance of the information rendered on the label, as well as to establish the feasibility of the quality assessment of the label, the market study has been performed using the method of questioning. The answers of 500 respondents have been analyzed and appropriate conclusions have been made. The incomprehensibility of the label has been identified as the main reason for ignoring the food product. The basic causes of violation of labeling norms have been established. The importance of clarity, accessibility and readability of the label for consumers has been underlined. The feasibility of quality assessment of the label as a constituent part of the final product has been confirmed. Based on the analysis of the survey results the label quality characteristics have been formulated and methods of their assessment have been developed.